Universidades Sustentáveis: ambientalização curricular no curso de Medicina da UNOESTE, Presidente Prudente-SP - AURÉLIO, Samuel Augusto Ferreira (2024)
This dissertation was developed within the Graduate Program in Environment and Regional Development, under the research line "Environmental Planning and Regional Development." Environmental education is a transdisciplinary field that seeks to promote a critical-dialogical view and understanding of environmental issues, as well as to develop skills and attitudes that lead to responsible and sustainable actions in relation to the environment, which makes Curricular Greening a transformative element for the relationship between human beings and the environment. In this context, the present research aims to verify how the proposal of Curricular Greening is developed in the Medicine course at the Presidente Prudente-SP campus of the University of Western São Paulo (Unoeste), analyzing how environmental issues are incorporated into this course. Thus, the study examines how the environmental question has been incorporated into the Course Pedagogical Project. Furthermore, it analyzes how the Curricular Matrices present environmental concerns by verifying the presence of greening indicators in the Course Syllabi, based on the Network of Curricular Greening of Higher Education. The research has a quantitative nature, beginning with an exploratory review of the literature on Curricular Greening in Medicine courses in Brazil. Subsequently, data was collected through a documentary analysis of the Course Pedagogical Project and the syllabi of the disciplines of the Unoeste Medicine course in Presidente Prudente-SP. The results show that Curricular Greening indicators are present in 75.7% of the courses. Among the disciplines investigated, it is observed that those in the fields of ethics, social interactions, and public health are more integrated with the greening indicators. On the other hand, the technical disciplines, to date, do not meet the same indicators. Thus, it is verified that the technical disciplines of the medicine course present an interesting opportunity for Curricular Greening to be expanded in the investigated course. Regarding the disciplines more closely related to social issues and marked by the indicators, it is noted that the course documents show a concern with greening derived from the analysis of socio-environmental problems and their impact on the analyzed context.